CLIMATIC FLUCTUATIONS DURING THE LAST GLACIAL IN THE NORTH-WESTERN LOMBARDIAN PREALPS: THE UPPER PLEISTOCENE FAUNAL ASSEMBLAGES OF THE CAVERNA GENEROSA (COMO, ITALY) (Rivista italiana di Paleontologia e Stratigrafia, 2009)
Since 1991, the Caverna Generosa was subject of numerous digging campaigns, principally in two areas called "Sala Terminale" and "Cunicolo 13-15". Dating of the first 6 stratigrafical levels of the 13 investigated in the "Sala Terminale" gave an age between 50.000 and 38.000 years BP (14C non calibrated dating). In the area of the "Cunicolo 13-15", between meters 13 and 15 from the entrance, seven stratigrafical levels were excavated, and bones coming from layers from II to V were dated between 37.000 and 31.000 years BP ago (14C non calibrated dating). Microvertebrates remains are used to infer paleoenvironmental and paleoclimatic information. The microfaunal assemblages of "Sala Terminale" testifies for a climatic improvement, during the period between over 50.000 y BP and 40.000 y BP: from a cold climate and an environment characterised by open vegetation to a wooded areas and milder temperature. This climatic improvement is also recorded in the lower level of "Cunicolo 13-15", probably subsequent to the top of the "Sala Terminale". Then, microfaunal associations became typical of cold climate. This climatic worsening had its maximum at the base of lev. Cun 0, during the last Pleniglacial. Therefore, the sediments of "Caverna Generosa" probably testify the climatic and faunal changes of the period between isotopic stage 4 and 1.